2006
DOI: 10.3758/bf03193360
|View full text |Cite
|
Sign up to set email alerts
|

Reinstating object-based attention under positional certainty: The importance of subjective parsing

Abstract: Previous studies have shown that interference from flanking distractors can be modulated by the object organization of the scene. The experiments reported here test for object-based attention under conditions of positional certainty, which allow a narrow focus of attention to the target. Prior research has suggested that object-based attention does not arise in these circumstances, but the experiments presented here show that object-based attention can still appear if previous experience with the stimuli leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
118
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(133 citation statements)
references
References 26 publications
12
118
2
1
Order By: Relevance
“…On the basis of their results, Richard et al proposed that the key factor in obtaining object-based attention under the condition of positional certainty was the perception of the task-relevant feature as an integral part of an object shape, rather than as something perceptually segregated from the object shape. It should be pointed out, however, that this interpretation did not explain why object effects were observed in other studies where the task-relevant feature was clearly not an integral part of an object shape (e.g., Chen & Cave, 2006. Regardless of what induced the object effects found in Richard et al, the finding of an object effect even when the location of the target was known in advance suggests that object effects are not just a by-product of the order in which different regions of a scene are visited during visual search.…”
Section: Mechanisms That Give Rise To Object Effectsmentioning
confidence: 55%
See 4 more Smart Citations
“…On the basis of their results, Richard et al proposed that the key factor in obtaining object-based attention under the condition of positional certainty was the perception of the task-relevant feature as an integral part of an object shape, rather than as something perceptually segregated from the object shape. It should be pointed out, however, that this interpretation did not explain why object effects were observed in other studies where the task-relevant feature was clearly not an integral part of an object shape (e.g., Chen & Cave, 2006. Regardless of what induced the object effects found in Richard et al, the finding of an object effect even when the location of the target was known in advance suggests that object effects are not just a by-product of the order in which different regions of a scene are visited during visual search.…”
Section: Mechanisms That Give Rise To Object Effectsmentioning
confidence: 55%
“…Although this prediction was confirmed in Shomstein and Yantis (2002), other studies have shown object effects when the location of the target was known in advance (e.g., Chen & Cave, 2006Harms & Bundesen, 1983;Kim & Cave, 2001;Kramer & Jacobson, 1991;Richard et al, 2008). Chen and Cave (2006) used an experimental paradigm similar to that used in Shomstein and Yantis (2002, Experiments 1-4), where the target always appeared at the center of a crosslike configuration. While no object effect was found when participants saw the full cross-like configuration on every trial, it was observed when that configuration appeared on only some of the trials, with the rest of the trials consisting of displays that showed only one or two of the three rectangles.…”
Section: Mechanisms That Give Rise To Object Effectsmentioning
confidence: 93%
See 3 more Smart Citations